Phenotypic screening with target identification and validation in the discovery and development of E3 ligase modulators. Issue 3 (18th March 2021) - Ege, Nil; Bouguenina, Habib; Tatari, Marianthi; Chopra, Rajesh
Summary: The use of phenotypic screening was central to the discovery and development of novel thalidomide analogs, the IMiDs (immunomodulatory drugs) agents. With the discovery that these agents bind the E3 ligase, CRL4 CRBN, and alter its substrate specificity, there has been a great deal of endeavor to discover other small molecules that can modulate alternative E3 ligases. Furthermore, the chemical properties necessary for drug discovery and the rules by which neo-substrates are selected for degradation are being defined in the context of phenotypic alterations in specific cellular systems. This review gives a detailed summary of these recent advances and the methodologies being exploited to understand the mechanism of action of emerging protein degradation therapies. Graphical abstract: Abstract : In this review, Ege et al. provide a detailed overview of the role of phenotypic screening to the discovery and development of E3 ligase modulators. It further summarizes recent advances and methodologies being exploited to understand the mechanism of action of emerging protein degradation therapies.